How Fast Do Old Men Slow Down? - Fair, Ray C. (The Review of Economics and Statistics, 1994)
Abrtmcr-An important question in the study of aging concerns the rate at which people physically deteriorate with age.HOW much, for example.CB be physically expected of, say, a healthy, non-injured 75.year-old man or woman relative to what be or she could do at ape 4% This paper applies econometric techniques to data on men's track and field and road racing remrds by age to estimate the rate at which men sknv down with asc.Eight track.eight field.and eleven road racing events me considered.The main econometric technique usad is a combination of the polytwmial-spline method and the frontier-function method.A number of the evetttr have been pooled to provide more et%cient estimates.1.